Strangulated left tubo-ovaran inguinal hernia - Vera-Portilla, Angel F. (2022)
Indirect inguinal hernia (IHH) is the most frequent congenital anomaly in infancy and childhood. In girls, the sliding IIHs contain mainly the ovary with or without a fallopian tube. We present the case of a 6-month-old girl who was presented with an irreducible left inguinal tumor associated with vomiting. She was operated of emergency with a diagnosis of complicated left indirect inguinal hernia containing gangrenous fallopian tube and left ovary. This type of hernia has a higher incidence in prematures and females under one year of age. Preoperative ultrasound may be helpful for diagnosis. The repair procedure is the classic herniorrhaphy with high ligation of the hernia sac, through an inguinal approach.